2002
DOI: 10.1023/a:1020974710389
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Chronic low-frequency stimulation (CLFS) of rat fast-twitch muscles induces sequential transitions in myosin heavy chain (MHC) expression from MHCIIb --> MHCIId/x --> MHCIIa. However, the 'final' step of the fast-to-slow transition, i.e., the upregulation of MHCI, has been observed only after extremely long stimulation periods. Assuming that fibre degeneration/regeneration might be involved in the upregulation of slow myosin, we investigated the effects of CLFS on extensor digitorum longus (EDL) muscles regene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…In contrast, a significant increase in MyHC-slow is induced after stimulation of the regenerating EDL muscle (ref. 33 and our unpublished observations), reflecting a greater plasticity of regenerating compared to mature muscle, as observed in other experimental settings (34,35). Interestingly, a MyHC-slow promoter-reporter construct is up-regulated by caNFATc1 in both regenerating and adult fast muscles.…”
Section: Discussionsupporting
confidence: 74%
“…In contrast, a significant increase in MyHC-slow is induced after stimulation of the regenerating EDL muscle (ref. 33 and our unpublished observations), reflecting a greater plasticity of regenerating compared to mature muscle, as observed in other experimental settings (34,35). Interestingly, a MyHC-slow promoter-reporter construct is up-regulated by caNFATc1 in both regenerating and adult fast muscles.…”
Section: Discussionsupporting
confidence: 74%
“…An important aspect of our study was that we identified that the slow-to-fast fiber transition of muscle fiber types in knee extensor muscle was reversible ( Figure 2 ). Apart from investigations with disused muscle in laboratory species ( Desplanches et al, 1987 ; Pette et al, 2002 ), the former phenomenon has to the best of our knowledge only been described in one human study with 12-weeks of strength training of young subjects after 3 weeks of immobilization ( Howald, 1982 ; Hortobagyi et al, 2000 ; Fluck and Hoppeler, 2003 ; Wilson et al, 2012 ). Our findings now indicate that the reestablishment of the normal fiber type distribution in ACL-insufficient patients in the physiological context of standard rehabilitation and self-motivated exercise may take years to complete.…”
Section: Discussionmentioning
confidence: 99%
“…These alterations may be accompanied by the rarefaction of capillaries ( Adair and Montani, 2010 ), and collectively reduce aerobic capacity and the capacity for force production ( Desplanches et al, 1987 ; Pette, 2001 ). Increasing contractile activity subsequent to disuse elevates the metabolic capacity of skeletal muscle by enhancing the volume content or density of mitochondria and capillaries, and capillary-to-fiber ratio, and reestablishes the normal distribution and cross sectional area of muscle fiber types [reviewed in ( Desplanches et al, 1987 ; Pette et al, 2002 ; Fluck and Hoppeler, 2003 )]. In a single example with young subjects it has been shown that slow-to-fast transformation also occurs in knee extensor muscle of human subjects with durations of immobilization as short as 3 weeks and can be reversed by subsequent strength training over a period of 12 weeks ( Hortobagyi et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies never examined whether Type I were formed as a consequence of the remodeling of Type II fibres or through the formation of new fibres, a process that would require satellite cells. Indeed the development of Type I fibres following extended CLFS can only be induced to significant levels when accompanied by robust myofibre regeneration ( Pette et al, 2002 ; Maier et al, 1988 ). Taken together, these studies imply that myostatin signalling acts at an embryonic/foetal stage of muscle development to pattern a subpopulation of satellite cells/muscle precursors in a muscle specific manner to form Type I fibres.…”
Section: Discussionmentioning
confidence: 99%